Talent identification and its role in tennis - Stojanovic, G.
From the literature I have reviewed it is clear that tennis involves an enormous range of factors that combine to produce a highly skilled performer. Some of these are; physical characteristics, physiological characteristics, skill levels, psychology, and others such as genetic, biological and sociological factors. Currently there is an absence of a comprehensive research base, TID is still largely a speculative process and increased research in the areas looked at by Abernathy and Russell would provide much needed background to the specific skills in tennis.